Linseed (Linum usitatissimum L) growth and yield influenced by boron and zinc application in central plain zone of Uttar Pradesh (International Journal of Food and Nutritional Sciences, 2020)
A field experiment was conducted during the Rabi season of 2020-21 at the AgronomyResearch Farm of Faculty of Agricultural Sciences and Allied Industries; Rama University,Kanpur Nagar, Uttar Pradesh. Three replications were used in the randomized block designexperiment